Enraizamento adventício de estacas de Sebastiania schottiana Müll. Arg. - Frassetto, Eduardo Garcia (2007)
The aim of this work was to verify the cuttings rooting potential of Sebastiana schottiana as mechanism of vegetative propagation. Cuttings were collected next to the edges of Soturno River, Faxinal de Soturno County, situated in the regions of Plateaus and central depression of the Rio Grande Do Sul State, Brazil. Plants donors of cuttings were 5 years of age old approximately. In the work were subdivided in of 4 tests. In experiment 1, cuttings were cut and classified in accordance with the position in apex, medium and basal portions, with 30 cm of length. Monthly collections of the material by a period of 12 months were made, being the cuttings placed in containers with water and 15 cm of cutting submerged. The percentage of rooting, number and length of roots, number and length of shoots were evaluated after 60 days. In experiment 2, basal, medium and apex cuttings collected in the month of September of 2005 were absorbed in solution of Orgasol®FTS in the dosages of 0; 5; 10 and 15 mL.L-1 during 1 minute and submerged 15 cm of cutting, in containers with sand of medium granulation. The rooting percentage, dry weight of roots and shoots, length and diameter of longer root were evaluated after 75 days. In experiment 3, collected basal and medium cuttings in the month of April of 2006 were absorbed in solution of 15 mL.L-1 Orgasol® FTS during 0, 15, 30 and 45 minutes and placed in plastic bags to a depth of 15 cm, having sand of medium granulation. The rooting percentage, dry weight of roots and shoots, number of longer and smaller root than 3 cm of length, length and diameter of the longer root were evaluated after 150 days. In experiment 4, two tests were carried out: (a) Cuttings removed from shoots with 15 cm of length were classified in basal or apical position. Cuttings were immerged in IBA solution (0, 1, 2, 4 and 8 mg.L-1) for 1 minute and placed in Plantmax® for 60 days in a Greenhouse. The rooting percentage, dry weight of roots and shoots, number of roots and shoots and the length of roots and shoots were evaluated, (b) Basal cuttings were disinfested and immersed during 24 hours in IBA soluction (0; 0.1; 1; 2; 4 and 8 mg.L-1) and placed in glass bottles with solution of ¼ of WPM medium for a period of 30 days in climatized room. In experiment 1, the basal cuttings (88%), medium (56%) and apex (25%) collected in the May month presented better rooting. The basal cuttings had showed greater number and length of roots and shoots during the 12 months of evaluation. In experiment 2, the dosage of 5 mL.L-1 did not stimulate the rooting, whereas the dosages of 10 and 15 mL.L- 1 caused an increase in the rooting of 18% until reaching in the dosage of 15 mL.L-1, 28%. All tested dosages, basal cuttings (26.25%) presented greater rooting than medium (20,83) and the apex (18.33%). In experiment 3, the increase of immersion time of the cuttings in solution of 15 mL.L-1 Orgasol®FTS, stimulated an increment in the rooting at basal cuttings of 25% for 36% and in the medium cuttings of 29% for 46%, as well as in the dry weight of roots and shoots and in the number of roots longer than 3 cm. In the experiment 4A, the basal cuttings presented greater rooting in the concentration of 4 mg.L-1 IBA (20.83%) and the apex cuttings in the 2 mg.L-1 IBA (12.35%). In the experiment 4B the better rooting of cuttings was in solution of 8 mg.L-1 IBA (18.75%). Transversal and longitudinal cuts of the rooting cuttings removed from shoots in experiment 4 were done. The adventitious roots of the cuttings originated to the xilematic vases, arround to pericycle cels.